Acts in Practice - Vincent, John, (Practice Interpretation ;, 2012)
In this volume, the second in the Practice Interpretation series, interpreters from various different situations describe how passages and themes in the book of Acts speak to their 21st-century circumstances. The aim in the words of a contributor is to "link up with some of the stories that belong to our lives today - things that are happening in the newspapers or in the churches, or in our own spiritual lives. to treat them as a springboard to make connections between Luke's world and ours" (Loveday Alexander). The 16 other contributors are John D. Davies, Susan Miller, Leslie Francis, Ian Wallis, Daniel McGinnis, David Holgate, Robin Pagan, Garnet Parris, Andrew Parker, Alan Powers, Neil Richardson, John Proctor, Christine Jones and John Vincent.